2009
DOI: 10.1016/j.bbamem.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin membrane domains in prokaryotes and eukaryotes

Abstract: Summary Cardiolipin (CL) plays a key role in dynamic organization of bacterial and mitochondrial membranes. CL forms membrane domains in bacterial cells, and these domains appear to participate in binding and functional regulation of multi-protein complexes involved in diverse cellular functions including cell division, energy metabolism, and membrane transport. Visualization of CL domains in bacterial cells by the fluorescent dye 10-N-nonyl acridine orange is critically reviewed. Possible mechanisms proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
291
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(304 citation statements)
references
References 91 publications
11
291
2
Order By: Relevance
“…Importantly, studies that previously reported abnormal mitochondrial morphology in ⌬crd1 and ⌬taz1 yeast never reported the penetrance of the observed defects (19,52). Furthermore, our results indicate that the genetic background contributes to mitochondrial morphology.…”
Section: Remodeling Is Not Required To Maintain Mitochondrialsupporting
confidence: 60%
See 2 more Smart Citations
“…Importantly, studies that previously reported abnormal mitochondrial morphology in ⌬crd1 and ⌬taz1 yeast never reported the penetrance of the observed defects (19,52). Furthermore, our results indicate that the genetic background contributes to mitochondrial morphology.…”
Section: Remodeling Is Not Required To Maintain Mitochondrialsupporting
confidence: 60%
“…4 a mitochondrial phospholipid with two phosphate headgroups and four acyl chains, is required for the optimal function of numerous mitochondrial processes, including oxidative phosphorylation (OXPHOS) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), protein import (14 -17), establishment of cristae morphology (18,19), fission and fusion (20 -22), and apoptosis (23,24). Despite limited acyl chain specificity of the CL biosynthetic enzymes (25,26), the acyl chain composition of CL within an organism or cell type displays a remarkable degree of homogeneity (27).…”
Section: Cardiolipin (Cl)mentioning
confidence: 99%
See 1 more Smart Citation
“…We used three different compositions of supported lipid bilayers: E. coli polar lipids (E. coli lipid bilayer), synthetic lipid mixture mimicking the head group composition of the E. coli polar lipids but with a synthetic mixture of 70% double-unsaturated and 30% monounsaturated aliphatic tail groups (18:2 bilayer), and a synthetic lipid mixture with 100% of the monounsaturated aliphatic tail groups (18:1 bilayer). The difference between lipid bilayers was in the lipid raft structure (28)(29)(30)(31) and fluidity of the membrane (SI Domain Structures in the Supported Lipid Bilayer, Fig. S1 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…The individual complexes contain several tightly bound phospholipid molecules that are integral to the structural integrity of each complex (11)(12)(13). The mitochondrial-specific phospholipid cardiolipin (CL) 5 is required for higher order organization of the individual complexes into supercomplexes (10, 14 -20); also see reviews (3,21). Understanding how the individual complexes are arranged in respirasomes and what role lipids play in respirasome formation and stability will provide information required for understanding the mechanism of electron transfer between individual complexes as well as the basis for dynamics of respiratory chain re-organization in the mitochondrial membrane.…”
mentioning
confidence: 99%